Podocarpus lambertii wood quality for the production of long fiber pulp - Vivian, Magnos Alan; Neto, Olavio Rosa; Duarte, Gabrielly Andrade; Paes, Scheila Terezinha da Silva; Moreira, Laiara Miguel; Modes, Karina Soares; Silva Júnior, Francides Gomes da; Dobner Júnior, Mário (Revista de Ciências Agroveterinárias, 2024)
The Brazilian forestry sector is based on the use of Eucalyptus and Pine wood, with emphasis on the latter in the state of Santa Catarina. Aiming to diversify the forestry base for industrial uses, and provide information on species that could be alternatives, studies aimed at characterizing wood are essential. In this sense, the species Podocarpus lambertii can be highlighted, which is a conifer native to the south of the country, and which has potential for use. Therefore, the present study aimed to evaluate the quality of P. lambertii wood with a view to producing long fiber cellulosic pulp. For this, five 26-year-old trees were collected, originating from an experimental planting located in Campo Belo do Sul/SC. Discs were removed from these to determine the basic and green densities, chemical composition and morphological analysis of the tracheids in the pith-bark direction. The basic (0.397 g/cm³) and green (0.907 g/cm³) densities obtained made it possible to classify the wood as light or low density. Regarding the chemical composition, ash (0.69%) and extractives (4.40%) contents were observed within the expected for coniferous wood, however the lignin content was high (36.99%), and low holocellulose content (58.61%). The dimensions of the tracheids, length (1.92 mm), width (35.06 μm), lumen diameter (25.55 μm) and cell wall thickness (4.75 μm), allowed them to be classified as moderately long and thick. The anatomical quality indicators, wall fraction (28.08%), flexibility coefficient (71.88%), Runkel index (0.41) and felting index (53.71), were considered very good for the pulp and paper production, based on classifications reported in the literature. In general, the results obtained were satisfactory, indicating that the species deserves attention and more in-depth studies, and could be an alternative or complement to the long fiber segment, which is currently supplied exclusively by the Pinus genus in Brazil.